2001
DOI: 10.1016/s0883-2927(00)00014-7
|View full text |Cite
|
Sign up to set email alerts
|

Radium geochemistry of ground waters in Paleozoic carbonate aquifers, midcontinent, USA

Abstract: The purpose of this study was to elucidate the processes controlling the distribution and behavior of the longerlived Ra isotopes in continuous Paleozoic carbonate aquifers of parts of Missouri, Kansas, and Oklahoma. Activities of ( 228 Ra) and ( 226 Ra) were analyzed in fresh and saline ground waters, brines, and rocks. The¯uids have a wide salinity range (200±250,000 mg l À1 total dissolved solids). The ( 226 Ra) activity ranges from 0.66±7660 dpm kg À1 and correlates with salinity and other alkaline earth e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
74
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(76 citation statements)
references
References 44 publications
(90 reference statements)
2
74
0
Order By: Relevance
“…The relatively high minimum values of apparent K D in fractured crystalline rocks (~10 3 ) indicate that Ra is rapidly adsorbed in fresh waters in bedrock fractures to balance input from alpha recoil, and that Ra does not exhibit the lower apparent K D commonly observed in sandstone aquifers (~10 1 -10 3 ; King et al, 1982;Lively et al, 1992;Reynolds et al, 2003) or saline aquifers (~10 0 -10 2 ; Sturchio et al, 2001). Net adsorption of Ra is less effective under the low-DO, higher-TDS conditions observed in this study because (1) anoxic fractures contain lower surface area of redox-sensitive Ra adsorption sites, such as Mn oxides; and/or (2) higher concentrations of alkaline earth metals, such as Ba, compete with recoil-generated Ra for adsorption sites.…”
Section: Overview Of Radionuclide Sources and Sinksmentioning
confidence: 99%
See 1 more Smart Citation
“…The relatively high minimum values of apparent K D in fractured crystalline rocks (~10 3 ) indicate that Ra is rapidly adsorbed in fresh waters in bedrock fractures to balance input from alpha recoil, and that Ra does not exhibit the lower apparent K D commonly observed in sandstone aquifers (~10 1 -10 3 ; King et al, 1982;Lively et al, 1992;Reynolds et al, 2003) or saline aquifers (~10 0 -10 2 ; Sturchio et al, 2001). Net adsorption of Ra is less effective under the low-DO, higher-TDS conditions observed in this study because (1) anoxic fractures contain lower surface area of redox-sensitive Ra adsorption sites, such as Mn oxides; and/or (2) higher concentrations of alkaline earth metals, such as Ba, compete with recoil-generated Ra for adsorption sites.…”
Section: Overview Of Radionuclide Sources and Sinksmentioning
confidence: 99%
“…Radium mobility or adsorption effectiveness is understood to vary with chemical parameters including pH (Cecil et al, 1987;Dickson and Herczeg, 1992;Bolton, 2000;Szabo et al, 2005), salinity (Kraemer and Reid, 1984;Sturchio et al, 2001;Wood et al, 2004), reduced conditions (Szabo and Zapecza, 1987;Herczeg et al, 1988), supersaturation with respect to barite (Gilkeson et al, 1984;Grundl and Cape, 2006), microbial sulfate reduction affecting barite stability (Phillips et al, 2001;Martin et al, 2003), and microbial Fe oxide reduction (Landa et al, 1991). Ra adsorption is a rapid influence in freshwater at nearneutral pH (Krishnaswami et al, 1982), but the effects of redox processes and relatively low ion concentrations on adsorption and desorption are not well constrained in existing field investigations.…”
Section: Introductionmentioning
confidence: 99%
“…Relatively high 228 Ra levels in springs and the N well ( 228 Ra/ 226 Ra [ 1) could be explained by differences in Th/U ratios in the host carbonate rocks, e.g., 232 Th could be concentrated within relatively insoluble residue (silicates, phosphates and hydroxides) left behind after dissolution of carbonate aquifer rock rich in 228 Ra (Sturchio et al 2001). Another mechanism is the preferential solubility of 238 U relative to 232 Th, which is more closely attached to aquifer solids or sands (Von Gunten et al 1996;Ivanovich and Harmon 1992).…”
Section: Radium and Groundwater Sourcesmentioning
confidence: 99%
“…Therefore, radium is significantly more mobile under reducing and acid conditions (Albu et al 1997;Ames et al 1983;Langmuir & Riese 1985;Martin et al 2003;Szabo & Zapecza 1991). Several studies revealed a positive correlation between radium and salinity or chloride (Gascoyne 1989;Herczeg et al 1988;Lauria et al 2004;Sturchio et al 2001), and between high radium content and low pH . Two isotopes of uranium ( 238 U and 234 U) are represented in the 238 U decay chain (fig 1).…”
Section: Introductionmentioning
confidence: 99%